B140 Implementing a standardised technique for adductor canal blockade for unicompartmental knee replacement in a tertiary orthopaedic centre. (11th August 2022) - Chater-Lea, P; Abdallah, M; Crowley, M
Abstract : Background and Aims: The ideal regional anaesthetic technique for unicompartmental knee replacement (UKR) should provide good analgesia without compromising patient ability to mobilise post-operatively. Various approaches to blockade site and volume have been considered 1 . Low volume ACB should avoid motor blockade of medial vastus nerve and inadvertent proximal local anaesthetic spread and quadriceps weakness. In our tertiary orthopaedic centre a standard operating procedure (SOP) was created advising low volume, low concentration adductor canal blockade (ACB) of the saphenous nerve with 10 ml 0.2% ropivacaine, alongside effective surgical local infiltration. Methods: This ethics-approved prospective audit reviewed records of around 30 consecutive patients undergoing UKR, and assessed whether ACB was performed, dose and volume of local anaesthetic used, and 24-hour post-operative opiate consumption. Two cycles were performed; one pre-SOP introduction, one six months post-introduction. For comparison, data were grouped as 'compliant with recipe, ' 'non-compliant' or 'no ACB performed.' Results: Pre-SOP, a total of 17 different ACB recipes were utilised, with large variations in post-operative opiate consumption. Re-audit showed utilisation of ACB in 70% of cases, and 57% compliance with SOP when ACB was performed. Post-operative opiate consumption decreased when ACB was compliant versus non-compliance, from 40.4mg to 22.5mg oral morphine equivalence. When ACB was not used, opiate consumption was markedly higher at 76mg. Conclusions: Appropriately sited low volume, low concentration ACB can improve patient experience post-UKR. Introduction of a local SOP in such patients has shown good clinician uptake in addition to reduced post-operative analgesia use. Further targeted clinician education will now aim to improve performance and patient outcomes.